Adsorption of alkyl benzene sulfonate surfactant on activated carbon for biobarrier purpose - Wijanarko, Anondho; Kencana Wulan, Praswasti Pembangun Dyah; Chandra, Willy; Dianursanti, Dianursanti; Song, Seung Koo; Sudibandriyo, Mahmud; Gozan, Misri (2006)
Simultaneous adsorption and biodegradation process in fluidized biobarrier reactor is one of emerging methods for eliminating surfactant in waste water. This paper discusses the adsorption process on activated carbon as a part of a biobarrier system. Surfactant used in these experiments is branched sodium dodecyl benzene sulfonate branched in various concentrations of 400, 700, 1000 and 1500 mg/L placed in 250 mL closed-erlenmeyer container (in batch system). Adsorption took part in a glass column of 30 cm length and 2 cm diameter. Total surfactant concentration was measured with COD-chromate analysis and surface tension measurement. Adsorption equilibrium curves in solid (dC/m) and liquid phase (Ce) as well as surfactant concentration versus surface tension were performed. The results showed that surfactant adsorption equilibrium curve rose within equilibrium concentration (Ce) 0 – 533.4 mg/L, then reached plateau with increasing Ce. Critical Micelle Concentration (CMC) Sodium Dodecyl Benzene Sulfonate was 533.4 mg/L. Freundlich equilibrium constants were (1/n) = 1.91 and Kf = 9.97.10-5 in Ce range of 252.6 to 481.2 mg/L. The equilibrium time for adsorption was 24 hours and the minimum fluidization velocity was predicted to be 0.717 cm/s.